how to solve -10≤2x-4≤6

Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

# how to solve -10≤2x-4≤6

i dont understand

## Research, Knowledge and Information :

Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

### How do you solve 10> - 2x + 4> - 6? | Socratic

... "reverse the inequality sign". 6/(-2) < (cancel(-2) x)/cancel(-2) < (-10)/ ... How do you solve #10> - 2x + 4> - 6#? Algebra. 1 Answer ? 1 Jim G ...

### 2x-4=6 - Get Easy Solution

Simple and best practice solution for 2x-4=6 equation. Check how easy it is, and learn it for the future. ... SOLVE: Solution for 2x-4=6 equation: 2x - 4 = 6

### 5 Ways to Solve for X - wikiHow

There are a number of ways to solve for x, ... Solve for x and 2x. Thanks! Yes No. Not Helpful 1 Helpful 3. How do I draw y = (x)+3? Donagan, Top Answerer

### 2x+10=4 - Get Easy Solution

Simple and best practice solution for 2x+10=4 equation. Check how easy it is, ... SOLVE: Solution for 2x+10=4 equation: 2x + 10 = 4 2x = 4 ...

## Suggested Questions And Answer :

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### 03,597I=102x-2

??????????? wotz the quesshun ?????????? maebee wanna solv for x ???? or for i????

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### factor 2y^2+y-10

2x^2 +x -10=0 (x-2)(x+2.5)=0

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### use the method of substitution to solve the linear equation

2x-y=2   so y=2x-2 9x -4y=10 9x -4*(2x-2)=10 9x-8x +8=10 x=2 y=2x-2=4-2=2

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### How do I solve y=-x-4

How do I solve y=-x-4 I need to be able to plot these points on a graph but i don't know how to solve the problem.   make an x & y axis. ( like a cross one line goes vertical an the other horizontal) put equal dimention for x & y line From center line moving

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### How do you solve this problem? solve for d: n= m+3d/4

Problem: How do you solve this problem? solve for d: n= m+3d/4 I need help solving this and seeing how it was solved since I am having trouble figuring out what to do and how to solve it thanks. n = m + 3d/4 n - m = (m + 3d/4) - m n - m = 3d/4 4(n - m) = (3d/4)4 4(n - m) = 3d 4(n - m)/3 = 3

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how can i solve these equations?

how can i solve these equations? x + 3y – z = 2 x – 2y + 3z = 7 x + 2y – 5z = –21 We eliminate one of the unknowns (x, y or z, take your choice), leaving two unknowns. Then, we eliminate a second one, giving us an equation with only one of the unknowns. Solve for that and plug that value in

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### Solve, using linear combination. 3x + y = 4 2x + y = 5

line 1: 3x+y=4    or y=4-3x line 2: 2x+y=5 line 1 -line2...(3x-2x)+(y-y)=4-5 or x=-1 y=4-3x=4+3=7

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### Inequalities

9x+6=51 9x=51-6 9x=45 x=5

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4)

#### Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
• Start your question with What, Why, How, When, etc. and end with a "?"
• Be clear and specific
• Use proper spelling and grammar